2007
DOI: 10.1111/j.1468-3083.2007.02204.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy is a suitable method for the observation of the pregnancy‐related changes in melanocytic nevi

Abstract: During the pregnancy, widening in diameters and structure changes of nevi may be seen especially on the front of the body. We also think that these findings might be connected with expansion of the skin during pregnancy. Dermoscopic controls are the first choice of method to analyse the nevi since the patient may not recognize these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…It has been shown that these changes linearly increase with the length of pregnancy and are most evident during the third trimester and at the time of delivery. [56][57][58][59] These changes also reverse themselves approximately 3 to 6 months after delivery, and so reexamination of nevi at that time is usually recommended. Since any change during a 3-month interval must be considered suspect, the physiologic changes of nevi should be taken into account when performing shortterm digital follow-up.…”
Section: Commentmentioning
confidence: 99%
“…It has been shown that these changes linearly increase with the length of pregnancy and are most evident during the third trimester and at the time of delivery. [56][57][58][59] These changes also reverse themselves approximately 3 to 6 months after delivery, and so reexamination of nevi at that time is usually recommended. Since any change during a 3-month interval must be considered suspect, the physiologic changes of nevi should be taken into account when performing shortterm digital follow-up.…”
Section: Commentmentioning
confidence: 99%
“…Another dermoscopic analysis was performed on 82 nevi of pregnant women from locations all over the body in the first and third trimesters. 13 Pattern analysis of these lesions revealed no significant differences between visits, but there was new dot development in 6 of the nevi, 4 of which were located on the front of the body. There was also a statistically significant increase in the total dermoscopy score between the first and third trimesters.…”
Section: Nevi During Pregnancymentioning
confidence: 97%
“…In 1 study, 97 nevi measured from 56 pregnant women showed a statistically significant increased diameter from the first to the third trimesters. 13 Of the 20 nevi that grew, 10 were located on the front of the body, 6 on the face and neck, 3 on the legs, and 1 on the back. The degree of enlargement was most significant for lesions on the front of the body.…”
Section: Nevi During Pregnancymentioning
confidence: 99%
“…They concluded that a changing pigmented lesion in the pregnant woman should be approached in the same way as in any patient. Most dermoscopic changes are due to the physiological extension of the skin during pregnancy [7,8]. Only pregnant women with dysplastic nevus syndrome require closer monitoring; their nevi tend to have a higher rate of clinical change during pregnancy [9].…”
Section: Discussionmentioning
confidence: 99%